Fluorescent Hyperbranched Polymers and Cotton Fabrics Treated with Them as Innovative Agents for Antimicrobial Photodynamic Therapy and Self-Disinfecting Textiles - Desislava Staneva; Paula Bosch; Petar Grozdanov; Ivanka Nikolova; Ivo Grabchev (Macromol, 2025)
The results of this study, which involved treating cotton fabrics with three fluorescent hyperbranched polymers modified with 1,8-naphthalamide (P1), acridine (P2), and dansyl (P3) groups, could have applications in the development of antimicrobial textiles with self-disinfecting ability. The polymers, dissolved in DMF/water solution, were deposited on the cotton fabric using the exhaustion method. The fabrics were thoroughly analyzed by reflection spectra, CIEL*a*b* coordinates, and color difference (∆E). The release of the polymers from the cotton surface was studied in a phosphate buffer with pH = 7.4 and an acetate buffer with pH = 4.5 at 37 °C for 10 h. It is shown that at pH = 7.4, the release of the three polymers occurs slowly (about 4–5%). In contrast, in an acidic medium, due to protonation of the tertiary amino group of 1,8-naphthalimide, P1 passes significantly more readily into the aqueous solution (35%). The possibility of singlet oxygen (1O2) generation by the polymers and the cotton fabrics treated with them under sunlight irradiation was followed using an iodometric method. The microbiological activity was investigated against Gram-positive Bacillus cereus and Gram-negative Pseudomonas aeruginosa as model bacterial strains in the dark and after irradiation with sunlight. The antimicrobial activity of the polymers increased after light irradiation, as 1O2 attacks and destroys the bacterial cell membrane. Scanning electron microscopy showed that a stable bacterial biofilm had formed on the untreated cotton surface, but treatment with hyperbranched polymers prevented its formation. However, many bacteria were still observed on the fiber surface when the microbial test was performed in the dark, whereas only a few single bacteria were noticed after the illumination. A virucidal effect against respiratory viruses HRSV-2 and AAdV-5 was observed only after irradiation with sunlight.